Organisational culture in a South African non-governmental organisation: the challenge of a changing environment - Dollar, Disa G (Rhodes University, Faculty of Humanities, Department of Psychology, 1999)
Using Schein's (1992) notion of organisational culture, this study explored the position of a South African nongovernmental organisation (NGO) in the changing environment of post-apartheid South Africa. The study pursued three central goals: to describe the organisational culture of a South African NGO; to examine the tensions that have emerged owing to the changing nature of the organisational culture; and to analyze the organisational culture in relation to the changing NGO environment. The basic assumptions of the organisation regarding networking, the relationship with the government, funders and funding, leadership, human resource development, and service delivery, were collected. A single case study design was employed, with a sample of eight participants (representing the four different sections of the NGO) being drawn. Data were collected through documentary analysis, a focus group, and eight individual interviews using the critical incident technique. Analysis was performed using various qualitative data analysis techniques. The researcher found that participants considered networking, a cooperative relationship with the government, a proactive approach to obtaining funding, effective leadership and human resource development, and a good reputation for service delivery, to be essential for NGO survival. NGO basic assumptions are undergoing a transformation process, and tensions exist between long-standing and emerging assumptions. It was found that the transformation of assumptions is enabling the NGO to adapt to the challenges of the changing environment.
Keywords: Psychology, Industrial -- South Africa; Non-governmental organizations -- South Africa